Encyclopaedia Britannica 2001 - Encyclopaedia Britannica, Inc. ([Australia] Britannica.com.au, 2001)
This database contains the complete text from the Britannica 32-volume print set, the content of the 2000 Britannica Book of the Year, more than 8,500 photos, maps, and illustrations, and direct access to Britannica.com, Britannica`s Web navigation and information service.
Features the New Oxford dictionary of English.
System requirements: Microsoft(R) Windows(R) 95, 98, 2000, ME, or Windows NT(R) 4.0; Pentium(R) 133 MHz or higher processor; 32 MB RAM minimum, 64 MB recommended 120 MB free hard drive space (plus 50 MB for IE 5.01); CD-ROM drive; SVGA monitor/display card 800X600, 16-bit colour; mouse; sound card and speakers recommended; printer recommended; internet access recommended.
Contains one (1) installation disc and two (2) data discs.
Keywords: Encyclopedias and dictionaries